Education on Diabetes Mellitus Foot Care with Booklets in Kampung Parung Ponteng RW 07 Desa Tajur Citeureup Bogor - Reny Deswita; Vinny Maulidia; Yuliyanti (PT FORMOSA CENDEKIA GLOBAL, 2022)
Diabetic foot is a disorder of the feet and lower legs of people with diabetes. Based on community survey data in Parung Ponteng Village in June 2022, it was found that 3% of diabetic foot sufferers were adults and 5% of the elderly with a cadre team of 5 people who had not received training from the health team in the form of diabetes mellitus foot care. The purpose of this activity is to increase the community's ability to prevent diabetes with booklets. This activity was carried out by providing health education about DM foot care with a booklet for 1 day, before the implementation was given the pretest contents of the booklet and after the posttest education. There were 115 participants in this education. The results of this community service found that there was an increase in knowledge of DM foot care with a booklet of around 69%. The community responds well to explanations about DM foot care 87%.